Dispossession and Violence. Rethinking the Human in Bioethics (Revista Iberoamericana de Bioética, 2021)
Vulnerability is a key topic in bioethics. How is vulnerability conceived has deep implications in relationships between patient, medical staff and researchers. Judith Butler’s thinking on vulnerability expose the theoretical problem of violence. If vulnerability is merely understood in terms of injury and risk it obliterates interdependency as its fundamental character. Thinking vulnerability as dependency and openness allow to move from protection of personal integrity towards an ethical demand of social minimization of violence.
Keywords: the human; vulnerability; violence; bioethics; Judith Butler